2019
DOI: 10.1590/0074-02760190217
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles isolated from Trypanosoma cruzi affect early parasite migration in the gut of Rhodnius prolixus but not in Triatoma infestans

Abstract: The protozoan Trypanosoma cruzi has the ability to spontaneously secrete extracellular vesicles (EVs). In this paper, T. cruzi EVs derived from epimastigote forms were evaluated during interaction with triatomine bugs Rhodnius prolixus and Triatoma infestans. T. cruzi EVs were purified and artificially offered to the insects prior to infection with epimastigote forms. No effect of EVs was detected in the parasite counts in the guts of both vectors after 49-50 days. On the other hand, pre-feeding with EVs delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…EVs are produced by the different life stages of T. cruzi ( da Silveira et al, 1979 ; Gonçalves et al, 1991 ; Cestari et al, 2012 ; Bayer-Santos et al, 2013 ; Nogueira et al, 2015 ; Ramirez et al, 2017 ; Caeiro et al, 2018 ; Ribeiro et al, 2018 ; Paranaiba et al, 2019 ; Rossi et al, 2019 ) and participate in parasite host interactions ( Marcilla et al, 2014 ; De Pablos et al, 2016 ; Diaz Lozano et al, 2017 ; Ramirez et al, 2017 ; Wyllie and Ramirez, 2017 ; de Pablos Torro et al, 2018 ; Retana Moreira et al, 2019 ; Cronemberger-Andrade et al, 2020 ). Figure 1 illustrates EVs in different T. cruzi life stages.…”
Section: T Cruzi Evsmentioning
confidence: 99%
See 2 more Smart Citations
“…EVs are produced by the different life stages of T. cruzi ( da Silveira et al, 1979 ; Gonçalves et al, 1991 ; Cestari et al, 2012 ; Bayer-Santos et al, 2013 ; Nogueira et al, 2015 ; Ramirez et al, 2017 ; Caeiro et al, 2018 ; Ribeiro et al, 2018 ; Paranaiba et al, 2019 ; Rossi et al, 2019 ) and participate in parasite host interactions ( Marcilla et al, 2014 ; De Pablos et al, 2016 ; Diaz Lozano et al, 2017 ; Ramirez et al, 2017 ; Wyllie and Ramirez, 2017 ; de Pablos Torro et al, 2018 ; Retana Moreira et al, 2019 ; Cronemberger-Andrade et al, 2020 ). Figure 1 illustrates EVs in different T. cruzi life stages.…”
Section: T Cruzi Evsmentioning
confidence: 99%
“…The lack of studies of amastigote EVs is expected since it’s intracellular location and the secreted material as it is often contaminated with host cell constituents. In both epimastigotes and trypomastigotes, EVs contain several surface components of the parasite involved in the parasite adhesion, invasion, and migration in the vector’s gut ( Nogueira et al, 2015 ; Ribeiro et al, 2018 ; Paranaiba et al, 2019 ; Cronemberger-Andrade et al, 2020 ). Trypomastigote EVs modulates T. cruzi infection and affect the protozoan ability to enter and escape the parasitophorous vacuole.…”
Section: T Cruzi Evsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study with EVs derived from epimastigotes indicated that they promoted the differentiation of the replicative forms into MTs ( Garcia-Silva et al., 2014 ). In another study, purified EVs from epimastigotes, given to two distinct triatomine insects prior to infection with epimastigotes, affected early parasite migration in the gut of Rhodnius prolixus but not in Triatoma infestans ( Paranaiba et al., 2019 ). As regards TCT, EVs derived from different T. cruzi strains were shown to trigger differential innate and chronic immune responses ( Nogueira et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have already shown that different stages of T. cruzi release EVs under physiological conditions. They modulate NO and cytokine production by macrophages and delay parasite migration in the gut of vector [29,30]. Here, several experiments evaluated the role of stress factors affecting EV release by T. cruzi trypomastigotes.…”
Section: Discussionmentioning
confidence: 99%